How static and kinetic meditation, with or without guidance, affect autonomic nervous system activity in novice meditators - Han, Jinwoo; Lee, Myungji; Kim, Teri (Frontiers in Psychology, 2025)
ObjectiveThis study explored the autonomic nervous system responses and perceived experiences of novice meditators during kinetic and static meditation.MethodsThirty-five participants completed both meditation types in randomized order. Each 20-min session included 10 min of guided and 10 min of unguided meditation. Heart rate (HR) and Heart rate variability (HRV) was recorded using the Polar H10 and EliteHRV apps. A visual analog scale (VAS) assessed focused attention, peace and calm, and drowsiness.ResultsFocused attention was significantly higher in kinetic meditation than in static meditation and was also higher during guided sessions. Static meditation induced greater drowsiness than kinetic meditation, especially in the unguided condition. All meditation conditions increased HR compared to rest, with guided meditation showing a higher HR than unguided meditation. HRV indices reflected increased sympathetic activity during guided meditation sessions, likely due to cognitive effort in maintaining attention and processing instructions.ConclusionFor meditation-naïve individuals, movement-based meditation with clear guidance may serve as a more accessible entry point. Kinetic meditation appears to facilitate attentional engagement while mitigating drowsiness, and may remain manageable even when self-administered without guidance. These findings provide an empirical basis for optimizing meditation intervention design, particularly for novice practitioners who may initially perceive meditation as inaccessible or impractical.